Parallel computational fluid dynamics new frontiers and multi-disciplinary applications : proceedings of the Parallel CFD 2002 Conference, Kansai Science City, Japan (May 20-22, 2002) - Parallel CFD Conference (2002 : Kansai Bunka Gakujutsu Kenkyεu Toshi, Japan); Matsuno, K. (Kenichi) (Amsterdam ; Boston : North Holland/Elsevier, 2003)
This volume is proceedings of the international conference of the Parallel Computational Fluid Dynamics 2002. In the volume, up-to-date information about numerical simulations of flows using parallel computers is given by leading researchers in this field. Special topics are "Grid Computing" and "Earth Simulator". Grid computing is now the most exciting topic in computer science. An invited paper on grid computing is presented in the volume. The Earth-Simulator is now the fastest computer in the world. Papers on flow-simulations using the Earth-Simulator are also included, as well as a thirty-two page special tutorial article on numerical optimization.
Cover -- Table of Contents -- Preface -- Acknowledgements -- Part 1: Invited Papers -- Chapter 1. Lattice Boltzmann Methods: High Performance Computing and Engineering Applications -- Chapter 2. Multi-Disciplinary Simulations and Computational and Data Grids -- Chapter 3. A Different Approach to Large-Eddy Simulation with Advantages for Computing Turbulence-Chemical Kinetics Interactions -- Chapter 4. Simulation of Combustion Dynamics in Gas Turbine Engines -- Chapter 5. A Substepping Navier-Stokes Splitting Scheme for Spectral/hp Element Discretisations -- Part 2: Earth and Space Global Simulations and Earth Simulator -- Chapter 6. An MHD Model for Heliospheric Studies -- Chapter 7. Computational Performance of the Dynamical Part of a Next Generation Climate Model Using an Icosahedral Grid on the Earth Simulator -- Chapter 8. Optimization of a MHD Dynamo Simulation Code Using the GeoFEM for the Earth Simulator -- Chapter 9. Performance of Atmospheric General Circulation Model Using the Spectral Transform Method on the Earth Simulator -- Chapter 10. Improving Computational Efficiency of 4D-VAR System for Global Ocean Circulation Study -- Chapter 11. Coupling Strategy of Atmospheric-Oceanic General Circulation Model with Ultra High Resolution and its Performance on the Earth Simulator -- Chapter 12. Parallel Architecture and its Performance of Oceanic Global Circulation Model Based on MOM3 to Be Run on the Earth Simulator -- Chapter 13. Design and Performance Analysis of an Ocean General Circulation Model Optimized for the Earth Simulator -- Chapter 14. Development of a Nonhydrostatic General Circulation Model Using an Icosahedral Grid -- Chapter 15. Zonally Implicit Scheme for a Global Ocean Model -- Chapter 16. Successful Achievement in Developing the Earth Simulator -- Part 3: Parallel Environments -- Chapter 17. Simulation of Combustion Problems Using Multiprocessor Computer Systems -- Chapter 18. Autonomic System for Dynamic Load Balancing of Parallel CFD -- Chapter 19. High-Speed Mass Storage System of Numerical Simulator III and it's Basic I/O Performance Benchmark -- Chapter 20. Construction of a Large Scale PC-Cluster Machine and its Application to Combusting Flow Analysis in Chemical Furnace -- Chapter 21. Aerodynamic Computation of a Scramjet Engine on Vector-Parallel Supercomputers -- Chapter 22. A New Approach to Scientific Computing with JavaSpace -- Chapter 23. Numerical Simulator III -- Building a Terascale Distributed Parallel Computing Environment for Aerospace Science and Engineering -- Chapter 24. Blood Flow Simulation in a Grid Environment -- Chapter 25. Parallelization Methods for Three-Dimensional Fluid Code Using High Performance Fortran -- Chapter 26. The Development Strategy of Super-Computer Calculations in Russia. -- Chapter 27. Reaching Equilibrium for Non-Cooperative Dynamic Load Balancing Applications -- Chapter 28. The Parallel Flux Module of the National Combustion Code on Dynamic Load Balancing Environment -- Part 4: Parallel Algorithms -- Chapter 29. Numerical Simulation of Reaction-Diffusion and Adsorption Processes in Porous Media Using Lattice Boltzmann Methods with Concurrent Visualisation -- Chapter 30. A Parallel Multilevel Finite Element Solver for Axial Compres.
Includes bibliographical references.
Keywords: Fluid dynamics -- Data processing -- Congresses; Parallel processing (Electronic computers) -- Congresses; Supercomputers -- Congresses; Electronic books